THU0346 Concomitant fibromyalgia in axial spondyloarthritis has a negative impact on tnf alpha blockers treatment effect in real life. (15th June 2017) - Moltό, A; Etcheto, A; Gossec, L; Perrot, S; Boudersa, N; Claudepierre, P; Roux, N; Berenbaum, F; Martin, A; Sparsa, L; Coquerelle, P; Soubrier, M; et al.
Abstract : Background: Coexisting fibromyalgia (FM) in axial spondyloarthritis (axSpA) can represent therapeutic challenges, particularly when evaluating the treatment effect of biologics (i.e. TNF alpha blockers (TNFb)). Indeed, since FM patients often report high levels of pain and disability there is the risk of classifying such patients as refractory to TNFb (ie, as not reaching a significant improvement in disease activity). Objectives: To evaluate the impact of concomitant FM on the TNFb treatment effect in axSpA. Methods: Design: Prospective observational national study with 2 visits 3 months apart (baseline and 12 weeks after TNFb initiation) (Predict-SpA study ClinicalTrials.gov: NCT03039088 ). Patients: axSpA patients (diagnosis according to treating rheumatologist) initiating a TNFb. Data collection: the FiRST questionnaire (Fibromyalgia Rapid Screen Test) which screens for FM, patients and disease characteristics and effectiveness measures (e.g. ASAS response components). Statistical analysis: FM positive screening was defined by a FIRST score ≥5/6; the primary efficacy outcome was the ASAS 40. Non-responder imputation and baseline observation carried forward imputation (for binary and continuous outcome variables, respectively) was performed. Impact of FM on the TNFb treatment effect was evaluated by multivariable logistic regression, with ASAS 40 as the dependent variable and FM as the independent variable; were also included in the model other factors previously reported in the literature as associated with treatment efficacy (i.e. X-ray and MRI sacroiliitis, abnormal CRP (>6mg/L), HLA B-27, smoking status, previous TNFb exposure, age<40 and male gender). Results: Among the 527 patients enrolled in the study, 508 patients were analysed. Mean age was 41.4 (±11.6), 237 (46.7%) were women, with a 6.1±8.5 mean disease duration. Among them, 192 (37.8%) were screened as FM by the FiRST questionnaire. Overall efficacy of the TNFb was good (ASAS40, 201/508 (39.6%)) though 50 patients (9.8%) patients discontinued the TNFb before the follow-up visit and were considered as non-responders. Patients with FM presented less frequently an ASAS 40 response (87/192 (45.3%) vs 171/316 (54.1%), for the FM vs non-FM groups according to the FIRST definition. Presence of FM was independently associated with poorer ASAS40 response (adjusted odds ratio, OR =0.5 [95% CI 0.3 – 0.8]) while X-ray sacroiliitis (1.8 [1.2 – 2.8]), abnormal CRP (1.6 [1.0 - 2.4]) and absence of previous exposure to TNFb (1.7 [1.1 – 2.6]) were found to be associated with an ASAS40 response. Conclusions: This study 1) confirms the "conventional" predisposing factors of TNFb treatment response such as X-ray sacroiliitis, abnormal CRP and absence of previous exposure to TNFb; and 2) suggests that concomitant FM influences treatment response. FM deserves to be screened in axSpA, in particular in case of a decision to initiate a TNFb therapy. References: Perrot S, Bouhassira D, Fermanian J; Cercle d'Etude de la Douleur en Rhumatologie. Development and validation of the Fibromyalgia Rapid Screening Tool (FiRST). Pain. 2010;150:250–6. Acknowledgements: The PredicSpA study was supported by MSD thanks to an unrestricted grant. Disclosure of Interest: None declared